2016
DOI: 10.1108/md-09-2013-0443
|View full text |Cite
|
Sign up to set email alerts
|

Abusive supervision and employee creativity

Abstract: Purpose – Prior researches have indicated that leadership had an important impact on employee creativity. However, the authors know little about the link between the dark side of leadership-abusive supervision, and employee creativity, as well as its underlying mechanisms. Combining psychological safety theory and social identification theory, the purpose of this paper is to examine the relationship between abusive supervision and employee creativity and the mediating role of psychological safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 65 publications
6
69
2
3
Order By: Relevance
“…Research on the relationship between psychological safety and creativity has yielded mixed findings (Liu et al, 2016), which indicates that although psychological safety has often been identified as a predictor of creativity, it also interacts with other variables to alter predicted relationships (Edmondson and Lei, 2014). However, research on the boundary conditions associated with the influence of psychological safety remains underdeveloped (Edmondson and Lei, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Research on the relationship between psychological safety and creativity has yielded mixed findings (Liu et al, 2016), which indicates that although psychological safety has often been identified as a predictor of creativity, it also interacts with other variables to alter predicted relationships (Edmondson and Lei, 2014). However, research on the boundary conditions associated with the influence of psychological safety remains underdeveloped (Edmondson and Lei, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although most research has indicated the mediating role of psychological safety in the relationship between leadership or behaviors and follower creativity (e.g., Carmeli et al, 2010), Li et al (2015) found no evidence for such a mediation process. Some scholars have built a sequential mediational model to account for the inconsistent findings in the literature (e.g., Liu et al, 2016; Gonçalves and Brandão, 2017). For example, Gonçalves and Brandão (2017) found that psychological safety mediates the relationship between humble leadership and psychological capital, which is then positively related to team creativity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study showed that OI significantly affects the relationship between mental integrity and organizational creativity (Liu et al, 2016). One of the studies has shown that customer orientation is a mediating variable in linking OI and job performance (He et al, 2015).…”
Section: Research Questionsmentioning
confidence: 99%